Strategi Peningkatan Kepatuhan Peserta Didik Dalam Pelaksanaan Praktik Klinik Melalui Optimalisasi Administrasi Pelayanan di RSUP Dr. Johannes Leimena - Sukur, Dilly Ardiany; Rahawarin, Mohamad Arsad; Selanno, Hendry (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to formulate strategies to improve students’ compliance during clinical practice through optimizing service administration at RSUP dr. Johannes Leimena, Ambon. A qualitative approach was applied using in-depth interviews, observation, and documentation, involving 17 respondents from hospital staff, academics, and health community representatives. The findings reveal that well-structured and transparent administration plays a crucial role in creating an orderly, efficient clinical environment that supports students’ professional character development. Factors contributing to low compliance include a lack of understanding of discipline, weak supervision, unclear administrative workflows, low motivation, and unpreparedness for complex clinical situations. Optimization strategies include implementing digital systems, providing clear SOP guidelines, and conducting administrative training before clinical rotations. These efforts are effective in fostering orderliness, discipline, and professional readiness among students. The study highlights the importance of collaboration between educational institutions and hospitals in developing modern, accountable, and sustainable administrative systems. The findings are expected to serve as a foundation for building a more effective and adaptive clinical learning model that prepares competent healthcare professionals to meet future challenges.